Disorders of fluid and electrolyte metabolism : focus on hyponatremia - Peri, Alessandro 1964-; Thompson, Christopher J.; Verbalis, Joseph G. (Basel : Karger, 2019)
It is well known that acute, severe hyponatremia is a life-threatening situation. However, there is growing evidence that mild and chronic hyponatremia may also have negative consequences. Gait disturbances, attention deficits, falls and fractures, and bone loss have all been reported, with increased mortality in almost every disease state if the patient is hyponatremic. This book has been written by key opinion leaders in the field and covers a spectrum of crucial aspects of hyponatremia, including a historical perspective, physiology and pathophysiology of water homeostasis, epidemiology of hyponatremia, and clinical features. A detailed description of all available therapies has been incorporated, with a guide to a clinician's approach to key therapeutic situations. Hyponatremia is a topic that encompasses all areas of medicine, so this book will be of interest to specialists such as endocrinologists, nephrologists and internists, but will also be a valuable resource for all clinicians who manage patients with hyponatremia.
Keywords: HIPONATREMIA